2018
DOI: 10.1016/j.ijsu.2018.02.064
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure wound therapy versus conventional wound dressings in treatment of open fractures: A systematic review and meta-analysis

Abstract: NPWT can significantly reduce the risk of infection in treatment of open fractures and accelerate their wound healing process. Some but not much evidence suggests that NPWT may possibly help reduce the severity of the limb injury and therefore provide a chance for the limb to avoid amputation. Use of NPWT in the flap area is probably safe, but should be carried out with caution. The advantage of NPWT over the conventional wound dressings still requires to be confirmed in the other aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 26 publications
0
58
0
2
Order By: Relevance
“…In this study, the timing of wound closure of the infection group was longer than that recommended, as some patients required NPWT to improve their wound conditions. Previous metaanalyses have concluded that NPWT not only reduces the infection rate but also reduces flap necrosis and flap revision rates [21,22]. By contrast, the WOLLF trial demonstrated that there was no improvement in wounds with NPWT and that delays in covering the fracture should be avoided [23].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the timing of wound closure of the infection group was longer than that recommended, as some patients required NPWT to improve their wound conditions. Previous metaanalyses have concluded that NPWT not only reduces the infection rate but also reduces flap necrosis and flap revision rates [21,22]. By contrast, the WOLLF trial demonstrated that there was no improvement in wounds with NPWT and that delays in covering the fracture should be avoided [23].…”
Section: Discussionmentioning
confidence: 99%
“…Only 13 analysed wound closure, the key outcome for this type of intervention. Of these, 10 came to a positive conclusion [163][164][165][166][167][168][169][170][171][172], while 3 did not [173][174][175]. More importantly, only 14 [163-166, 168, 169, 171, 173, 175-180] of the 30 previous systematic reviews at least mentioned the risk of publication bias and none implemented any consequences for their conclusions in the event of this type of bias.…”
Section: Comparison With Previous Researchmentioning
confidence: 99%
“…The use of negative pressure wound therapy has been widely practised in the last two decades, in the USA and many countries [13], probably because of the increased understanding of its mechanism of action and also larger studies which support its critical role in wound management as compared to conventional dressings [14]. In the early nineties, Prof. S.A. Malik (unpublished data) introduced a local made version of negative pressure therapy in Pakistan to overcome the cost and burden of patients and hospitals.…”
Section: Discussionmentioning
confidence: 99%